2020
DOI: 10.1016/j.parkreldis.2020.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral alpha-synuclein levels in patients with genetic and non-genetic forms of Parkinson's disease

Abstract: Background: Variations of α-synuclein levels have been reported in serum and plasma in Parkinson's Disease (PD) Patients.Methods: Serum and plasma were obtained from PD patients without known mutations (GU-PD, n=124)), carriers of the A53T/G209A point mutation in the αsynuclein gene (SNCA) (n=29), and respective age-/sex-matched controls. Levels of total α-synuclein were assessed using an in-house ELISA assay.Results: A statistically significant increase of α-synuclein levels was found in serum, but not plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
(54 reference statements)
2
8
0
Order By: Relevance
“…Although small variations in plasma α‐synuclein levels were observed in GBA‐PD and NM‐PD compared with HC, no statistical differences emerged among groups, showing that this parameter is not distinctive for the GBA‐PD condition and confirming its unreliability as a surrogate marker of synucleinopathy 19,20 . Conversely, we found significantly higher exosome‐associated α‐synuclein in both PD groups compared with HC, in line with previous studies that specifically associated increased exosomal α‐synuclein with PD 12,21,22 .…”
Section: Discussionsupporting
confidence: 89%
“…Although small variations in plasma α‐synuclein levels were observed in GBA‐PD and NM‐PD compared with HC, no statistical differences emerged among groups, showing that this parameter is not distinctive for the GBA‐PD condition and confirming its unreliability as a surrogate marker of synucleinopathy 19,20 . Conversely, we found significantly higher exosome‐associated α‐synuclein in both PD groups compared with HC, in line with previous studies that specifically associated increased exosomal α‐synuclein with PD 12,21,22 .…”
Section: Discussionsupporting
confidence: 89%
“…Since exosomes are considered as potential carriers of toxic proteins, their role in PD pathogenesis has been extensively studied via the measurement of their levels in patient-derived biological fluids. Specifically, it has been demonstrated that although the levels of αSyn in the CSF of PD patients were lower compared to controls, the exosome-associated αSyn in the plasma of these patients was significantly higher [ 115 , 116 , 117 , 118 ]. As mentioned above, PD pathogenesis is closely linked to lysosomal function, with up to 7% of patients carrying a loss-of-function mutation in the GBA1 gene that encodes for the lysosomal enzyme β-glucocerebrosidase (GCase) [ 119 , 120 , 121 ].…”
Section: A Key Role Of Exosomes In Alpha-synucleinopathiesmentioning
confidence: 99%
“…A number of studies have sought uid biomarkers for synucleinopathies) [197][198][199][200][201][202], but reliable biomarkers are not yet widely available. Recently, biomarkers directly assessing α-synuclein have been developed using RT-QuIC or PMCA.…”
Section: α-Synuclein Strains As Potential Biomarkersmentioning
confidence: 99%